Implementation Of International Trade And Its Implications For Changes In National Business Views - Faizal Islam Akbar Alam; Nurul Asfiah (Pusat Riset dan Inovasi Nasional, 2024)
This research uses a bibliometric approach from international publication data accessed from the Google Scholar database which can be accessed via Harzing's Publish or Perish. Data collection was carried out by searching publications on Google Scholar regarding international trade and its coercion for responsible business with the keywords